Kopi, Kamu, dan Kita: Potret Peningkatan Pemahaman Konsep Legal Protection bagi Petani Kopi Terdaftar Indikasi Geografis di Desa Tlahap Kledung Temangggung Berbasis Multi-Sektoral - Waspiah, Waspiah; Rodiyah, Rodiyah; Latifiani, Dian; Arifin, Ridwan (Jurnal Pengabdian Hukum Indonesia, 2020)
Coffee is one of the leading commodities for Indonesia. The growth of coffee farming throughout Indonesia has also increased significantly in line with the growing trend of love for coffee on a national and international scale. This paper aims to discuss and explain the legal protection of coffee farmers registered with geographic indications in Tlahap Village, Kledung Temanggung, Central Java. This paper describes and analyzes various efforts to increase understanding of legal protection of geographic indications for coffee farmers. The method used in this program is direct assistance to coffee farmers in Tlahap Village and evaluation through interviews and surveys. The program found that the main obstacle faced by geographically indicated coffee farmers in Tlahap Village is human resources. The absence of a certified party to control coffee quality is one of the obstacles faced, in addition to the constraints of the geographical indication coffee farmer organizational structure. In addition, this program emphasizes that by increasing the understanding of legal protection for coffee farmers with geographical indications, the farmers are able to have readiness to face various obstacles in the field, one of which is regarding brand disputes, label fraud, and other legal problems. This program concludes that in terms of legal protection, cross-sectoral cooperation between farmer associations, government agencies and universities is required.